Certificateless Cross-Domain Group Authentication Key Agreement Scheme Based on ECC. (5th December 2022) - Cao, Liling; Liang, Mei; Zhang, Zheng; Cao, Shouqi
Abstract : Focusing on the problem that existing traditional cross-domain group authentication schemes have a high complexity, a certificateless cross-domain group authentication key agreement scheme based on ECC is proposed. The protocol provides scalability and can meet the requirements of cross-domain key negotiation by multiple participants in different domains. Security analysis shows that the proposed scheme is secure in the random oracle security model, it can resist some attacks under the extended Canetti-Krawczyk (eCK) security model. Performance analysis shows that the proposed scheme is of strong practical application value with high efficiency; it costs relatively low amount of calculation and communication.